2011
DOI: 10.1681/asn.2010050515
|View full text |Cite
|
Sign up to set email alerts
|

Local Renal Autoantibody Production in Lupus Nephritis

Abstract: Autoantibodies are central to the pathogenesis of several autoimmune diseases including systemic lupus erythematosus. Plasma cells secrete these autoantibodies, but the anatomical sites of these cells are not well defined. Here, we found that although dsDNA-specific plasma cells in NZB/W mice were present in spleen and bone marrow, a large number were in the kidneys and their number correlated with the serum dsDNA-IgG titer. We observed renal plasma cells only in mice with nephritis, where they located mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 54 publications
9
90
1
3
Order By: Relevance
“…Because BXSB also had B cells in the glomerulus, the BXSB genomic background rather than the Yaa mutation might have a role in the infiltration of B cells in the glomerulus. Studies on lupus models have demonstrated that infiltrating B cells in the kidney secrete antibodies with various antigen specificities, contributing to increased in situ immune complexes [29]. Recent reports have suggested that depleting B cells either before or after disease onset prevented and/or delayed the onset of nephritis in several different lupus model mice [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Because BXSB also had B cells in the glomerulus, the BXSB genomic background rather than the Yaa mutation might have a role in the infiltration of B cells in the glomerulus. Studies on lupus models have demonstrated that infiltrating B cells in the kidney secrete antibodies with various antigen specificities, contributing to increased in situ immune complexes [29]. Recent reports have suggested that depleting B cells either before or after disease onset prevented and/or delayed the onset of nephritis in several different lupus model mice [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…71 Such B cells undergo intrarenal proliferation and activation, which contributes to local inflammation and tissue pathology in addition to their role for systemic and intrarenal autoantibody production. 26,72,73 These data provide a rationale for B celltargeted therapies in LN. 74,75 T cell infiltrates also contribute to immunopathology in LN, particularly IL-17 producing CD3 + /CD4 + or CD3 + CD4/8 2/2 T cells.…”
Section: Intrarenal Pathogenic Mechanisms Of Lnmentioning
confidence: 93%
“…These are often organized along with T cells and DCs into lymph node-like structures that are known as tertiary lymphoid tissues (151,153,154). B lymphocytes within these structures are actively dividing (supported by local BAFF and APRIL), are undergoing somatic hypermutation, and sometimes form germinal centers (151,(153)(154)(155).…”
Section: Role In Gnmentioning
confidence: 99%
“…These are often organized along with T cells and DCs into lymph node-like structures that are known as tertiary lymphoid tissues (151,153,154). B lymphocytes within these structures are actively dividing (supported by local BAFF and APRIL), are undergoing somatic hypermutation, and sometimes form germinal centers (151,(153)(154)(155). The presence of germinal centers is strongly associated with tubular basement membrane immune complexes, providing a highly plausible link between local B-lymphocyte activation and progression of lupus nephritis in humans (151,153,154).…”
Section: Role In Gnmentioning
confidence: 99%